2015
DOI: 10.1118/1.4927717
|View full text |Cite
|
Sign up to set email alerts
|

A treatment planning study to assess the feasibility of laser‐driven proton therapy using a compact gantry design

Abstract: Under the analyzed terms, it is feasible to achieve clinically relevant dose distributions with laser-driven proton beams. However, to keep the delivery times of the proton plans comparable to conventional proton plans for typical target volumes, a device is required which can modulate the bunch intensity from shot to shot. From the laser acceleration point of view, the proton number per bunch must be kept under control as well as the reproducibility of the bunches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It is recognized that there are significant challenges ahead before laser-driven ion beams capable of meeting therapeutic specifications, both in terms of energy, repetition rate and general reliability, may become available. However, several authors have started to consider how a laser-driven treatment could be delivered, for example designing reduced size magnetic delivery systems (gantries) [94] or developing treatment plans tailored to the characteristics of TNSA beams [95,96]. Another significant development in this area is the future availability of laser-driven proton beamlines with controlled output parameters, which will allow significant progress in preclinical work (e.g.…”
Section: Cancer Therapymentioning
confidence: 99%
“…It is recognized that there are significant challenges ahead before laser-driven ion beams capable of meeting therapeutic specifications, both in terms of energy, repetition rate and general reliability, may become available. However, several authors have started to consider how a laser-driven treatment could be delivered, for example designing reduced size magnetic delivery systems (gantries) [94] or developing treatment plans tailored to the characteristics of TNSA beams [95,96]. Another significant development in this area is the future availability of laser-driven proton beamlines with controlled output parameters, which will allow significant progress in preclinical work (e.g.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Subsequently, a pillar beam-line was required to distinguish the dissimilar particle beam with an energy range directing this beam to the patient and considers a defined dose delivery. In order to empower a patient particle delivery, the beam-line should offer an energy choice framework to pick the desired parts from the primary particle spectrum [6]. Moreover, citing the ions as proper transducers, the Bragg curve of three ions: Carbon, Neon, and Oxygen was illustrated and compared respectively and it was demonstrated that Oxygen ion is the best particle in Hadron therapy due to its minor energy dissipation through matter on its path to the tumor.…”
Section: This Amount Of Ion Beams Advances the Arrangement Of Onementioning
confidence: 99%
“…Delivery of a clinical dose has been studied for axial clustering. Supposing a typical TNSA energy spectrum from a laser accelerator is transported through the suggested gantry (Figure 3), the number of beam pulses for patient irradiation is dependent on the number of protons accelerated by the laser [27]. For an initial proton number of about 3 Â 10 9 treatment plans with a sufficiently small number of pulses can be generated for small or medium sized tumors.…”
Section: Dose Delivery Proceduresmentioning
confidence: 99%
“…For an initial proton number of about 3 Â 10 9 treatment plans with a sufficiently small number of pulses can be generated for small or medium sized tumors. Pulseto-pulse fluctuations in the initial proton number may cancel in some cases [27], but exact stability requirements need further investigation. Additionally, the laterally clustering has to be considered.…”
Section: Dose Delivery Proceduresmentioning
confidence: 99%